The Effect of ESG Disclosure on Cost of Debt (An Empirical Study on Manufacturing and Energy Sector Companies Listed on the Indonesia Stock Exchange in 2019–2023) - Alayda Nur Puspita; Sri Hasnawati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates the impact of Environmental, Social, and Governance (ESG) disclosure on the cost of debt among manufacturing and energy sector companies listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023. Using a quantitative approach, the research analyzes ESG scores sourced from the Bloomberg Terminal and financial data from company reports. The panel data regression model tests both the aggregate ESG disclosure and individual ESG components—environmental, social, and governance—against the cost of debt, with control variables including firm size, profitability, leverage, liquidity, and the BI interest rate. The findings reveal a significant positive relationship between overall ESG disclosure and the cost of debt, suggesting that higher ESG engagement may be perceived by creditors as increasing financial burden or risk. Among the ESG components, only social disclosure significantly raises the cost of debt, indicating potential concerns from lenders regarding resource allocation for social activities. In contrast, environmental and governance disclosures showed no significant impact. The results challenge prior assumptions that stronger ESG performance universally reduces financing costs. Additionally, the BI interest rate also significantly influences debt cost, while other control variables do not. These outcomes underscore the complexity of ESG valuation in emerging markets like Indonesia, where regulatory compliance, market perception, and strategic motives intersect. The study contributes to a nuanced understanding of ESG disclosure effects in the corporate debt market and suggests further exploration of sector-specific and regional ESG practices.